Preparation and Evaluation of Hydrogels Containing Methanolic Extract of Brassica Oleracea ver. Italic - Tahir Ansari (Journal of Global Pharma Technology, 2016)
Objective: Herbal medicine usage is increasing nowadays because their usage is acceptable by most people to be safe and produce fewer side effects than synthetic drugs. This present study has been undertaken with the aim to formulate and evaluate herbal gel containing Brassica oleracea ver. italica methanolic extract. Method: The gel formulation was designed by using methanolic extract of Brassica oleracea var. italica, Carbopol 940, propylene glycol, methyl paraben, propyl paraben and required amount of distilled water. PH of skin was maintained by adding tri-ethanolamine drop wise. The prepared herbal gel formulation was subjected to preliminary evaluation such as pH, total phenolic content and total flavonoid content, viscosity, drug diffusion study and anti-inflammatory study. Result: The result of anti-inflammatory study showed that the gels with extract concentration of 1000 µg/ml have comparable anti-inflammatory activity with the Diclofenac sodium (100 µg/ml).Conclusion: Formulation of gel containing B. oleracea var. italica extract is a good attempt as herbal formulation has high demand in the market.Keywords: Brassica oleracea var. italica, Carbopol 940, Hydrogel.